Increasing the Possibilities of using Digital Technologies in the Development of Trade Services in the Republic of Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the specific characteristics of trade services in our country, the importance of trade in the economic potential of the country, the sharp increase in trade turnover using digital technologies in the development of trade services, and measures to increase the trade turnover several times in the future are being developed.In addition, in this article, suggestions and recommendations have been developed by the author on the improvement of trade services using digital technologies.